Doing things differently: an appreciation of Meltzer's contribution*. Issue 1 (2nd January 2016) - Rustin, Margaret
Abstract : In this paper I wish to draw attention to aspects of Donald Meltzer's ways of working which characterised his practice as a psychoanalyst and which I consider important in appreciating his originality. Several central themes are described and elaborated including: the central relevance of child analysis and the unity of child and adult analysis; the value of working in a clinical group with colleagues; the revision of psychoanalytic theory; joint research and writing projects; Meltzer's recognition of the power of infant observation as a tool for learning; the commitment to a wider psychoanalytic culture; the particular contribution to the Tavistock child psychotherapy training. Examples from Meltzer's written archive, both his books and papers, are used to demonstrate and illuminate these themes, alongside clinical material from child psychotherapy work brought to the author's attention in supervision.